Relations between Kazakhstan and Azerbaijan in the Current Geopolitical Environment: Analysis and Perspectives for Development (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
Kazakhstan and Azerbaijan are located in the region of Central Asia and the Caucasus, which gives them significant strategic importance. Given changes in the global political environment, such as energy security, regional stability and integration initiatives, the relationship between the two states takes on a new dynamic. Both states are producers and exporters of energy resources, including oil and gas, which creates opportunities for cooperation in this field. One important aspect of interaction between the two states is the development of the Central Corridor, which is a transport route connecting Kazakhstan and Azerbaijan across the Caspian Sea. However, today, despite the fact that Kazakhstan is one of the largest producers and exporters of energy resources such as oil and gas, it still maintains a certain dependence on Russia in the energy sphere. Kazakhstan seeks to diversify its energy resources and export routes in order to reduce its dependence on Russia. Thus, the purpose of this study is to analyze and understand the relationship between Kazakhstan and Azerbaijan in the new geopolitical environment, and to consider the challenges associated with the development of the Central Corridor. To achieve this purpose, the following objectives are set: to analyze diplomatic relations, economic cooperation and common interests, goals and priorities in the context of the new geopolitical environment; to examine changes in the global political environment, such as energy security, regional stability and integration initiatives; and to explore measures and initiatives taken by Kazakhstan and Azerbaijan to develop a mutually beneficial partnership in the new geopolitical environment and develop the Central Corridor.Key words: Kazakhstan, Azerbaijan, Central Corridor, geopolitics, oil and gas products.